PENERAPAN VIDEO CONTENT PEMBELAJARAN TEMATIK DALAM PENINGKATAN HASIL BELAJAR MENGAJAR DARING DI MADRASAH IBTIDAIYAH NEGERI 1 TEMBILAHAN - Rinda Luthfiana; Muannif Ridwan; Mahluddin Mahluddin; Muhaiminah Jalal (IndraTech, 2021)
This study discusses the application of learning video content in improving online teaching and learning outcomes. The focus of this research is on three things, namely the use of thematic learning video content media at Madrasah Ibtidaiyah Negeri 1 Tembilahan, the effectiveness of thematic learning using learning content videos, and student learning outcomes at Madrasah Ibtidaiyah Negeri 1 Tembilahan on video material using thematic learning content media. The method used is descriptive qualitative. This study concludes that the application of video content as a learning media is considered effective in increasing the effect of online learning, as evidenced by the results of interviews with principals, teachers, and students that this shows student performance is improving. The use of learning video content can also increase students' attention, make the learning atmosphere more fun, and attract students' interest in learning and make it easier for students. The benefits of this kind of learning media can be feedback to students so that it can help students obtain the availability of enlightening images and audio. Despite the shortcomings, there are still some videos that are not suitable for public viewing and hate speech that often appears in the comments column. As a suggestion in this study, schools should provide teachers with socialization activities related to the use of video media so that they all understand better that video media will affect student interest and learning outcomes.Keywords: application, video content, online learning.